7-5c=c+27

Simple and best practice solution for 7-5c=c+27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-5c=c+27 equation:


Simplifying
7 + -5c = c + 27

Reorder the terms:
7 + -5c = 27 + c

Solving
7 + -5c = 27 + c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1c' to each side of the equation.
7 + -5c + -1c = 27 + c + -1c

Combine like terms: -5c + -1c = -6c
7 + -6c = 27 + c + -1c

Combine like terms: c + -1c = 0
7 + -6c = 27 + 0
7 + -6c = 27

Add '-7' to each side of the equation.
7 + -7 + -6c = 27 + -7

Combine like terms: 7 + -7 = 0
0 + -6c = 27 + -7
-6c = 27 + -7

Combine like terms: 27 + -7 = 20
-6c = 20

Divide each side by '-6'.
c = -3.333333333

Simplifying
c = -3.333333333

See similar equations:

| 24=5y+3y | | 4(x+3)+2=2(x-3) | | (4x^5+3y)dx-xdy=0 | | -100=4k-8(2+2k) | | 3x+2=1+2x | | 2x-3=37-3x | | .5(x)4=48 | | r-6-26=13 | | sqrt(25)=x | | -2p-3(4-3p)=4(p-3)-12 | | 2x+11y=19 | | x(x)-6=13 | | 4y(3y+3)=118 | | 4x^4+2x^2-6=0 | | 3x-2x^2-4=0 | | -19=11-6X | | (4x-2)4x-2+5x(5x)= | | -5y-7(9y+7)=1+3(-7-y) | | y-9(5)=3 | | 4x^2+0.2x+0.01=0 | | 4(u+1)-7=3(u-1)+7 | | -x+3.9forx=-7.2 | | (4x+2)=-34 | | 9+4(-4)+3=-4 | | (4x+2)=34 | | 0.80x+0.20(60)=0.40(78) | | -3.6-7.2=12.7-6.1b | | (4x-2)(4x-2)+(5x)(5x)= | | 10x-4-6x=5x-7 | | (-10)+4=-2(-10)+-6 | | 2a+8=4a+16 | | 5(4x-4)-9=-31 |

Equations solver categories